2019
DOI: 10.33480/techno.v16i2.751
|View full text |Cite
|
Sign up to set email alerts
|

Penerapan Sistem Pendukung Keputusan Pemilihan Jurusan Dengan Metode Vikor Pada SMK Pariwisata Depok

Abstract: Abstract— The choice of majors is very important for vocational high school students. There are several factors that influence the decision making of majors. Therefore the writing of this thesis has the purpose of, among others, helping vocational high schools to be able to choose majors in accordance with the wishes and abilities of students. The purpose of writing this thesis is one of the graduation requirements for the Strata Satu (S1) program for the Nusa Mandiri Jakarta (STMIK) program. To achieve the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…The last step of the results obtained S and R values are calculated vikor, here if the alternative value gets the smallest vikor index value then the best value. S value 1 Jasa Boga (A3) 1 2 Administrasi Perkantoran (A2) 0,633 3 Akomodasi Perhotelan (A1) 0,5 4 Teknik Komputer Jaringan (A4) 0,329 Sources: (Nur & Susliansyah, 2019) From the above table 6, it is found that alternative 4 (Computer Network Engineering) has the smallest vikor index, 0.329. So alternative 4 (Computer Network Engineering) is ranked 1 in the process of completing the vikor method…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The last step of the results obtained S and R values are calculated vikor, here if the alternative value gets the smallest vikor index value then the best value. S value 1 Jasa Boga (A3) 1 2 Administrasi Perkantoran (A2) 0,633 3 Akomodasi Perhotelan (A1) 0,5 4 Teknik Komputer Jaringan (A4) 0,329 Sources: (Nur & Susliansyah, 2019) From the above table 6, it is found that alternative 4 (Computer Network Engineering) has the smallest vikor index, 0.329. So alternative 4 (Computer Network Engineering) is ranked 1 in the process of completing the vikor method…”
Section: Resultsmentioning
confidence: 98%
“…The second step is to weight criteria (Nur & Susliansyah, 2019) 5. The next step in the calculation of each alternative is multiplied by the weight of the result as follows (Nur & Susliansyah, 2019) 6. The next step is to calculate the S value of each alternative above.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This method is used to solve problems that are based on conflicting or incompatible criteria. This method focuses on the ranking and selection of various alternative criteria that can conflict with each other in the decisionmaking process [4]. The following steps will be taken to calculate using the VIKOR method [5], [6], [7], [8]:…”
Section: Methods Vikor (Višekriterijumsko Kompromisno Rangiranje)mentioning
confidence: 99%
“…Tujuan adanya club belajar di dalam suatu instansi pendidikan biasanya ditujukan guna pengembangan kreativitas dan karir sesuai dengan kebutuhan khusus peserta club belajar [2]. Saat ini proses penentun studi club masih menggunakan cara manual sehingga membutuhkan waktu yang lama karena harus mencatat data nilai mahasiswa, minat dan juga kreativitas mahasiswa [3].…”
Section: Pendahuluanunclassified